ANALISIS DAN SINTESIS BUNYI PETIKAN KALIMBA MENGGUNAKAN TRANSFORMASI FOURIER - Abd Djamil Husin; Indriyanti Rahmi Setyani; Sidikrubadi Pramudito; Sitti Yani; Ardian Arif Setiawan (Indonesian Physics Communication, 2023)
This research aims to analyze the sound produced by kalimba plates using the Fourier transformation. This research went through two stages, namely the analysis stage and the synthesis stage. The kalimba plate is plucked with variations in the applied force of 2 N to 5.5 N. The sound of the kalimba pluck is recorded using a sound sensor connected to PASCO Capstone software so that a deviation graph is produced as a function of time. The data obtained was then analyzed using Octave software. The research results show that the frequency is directly proportional to the damping coefficient value. The higher the frequency, the higher the frequency spectrum will be widened. The resulting Fourier coefficients only capture the values of the fundamental harmonic frequencies. This is because the kalimba plate has high rigidity.